Chlordecone potentiates hepatic fibrosis in chronic liver injury induced by carbon tetrachloride in mice. (25th July 2016) - Tabet, Elise; Genet, Valentine; Tiaho, François; Lucas-Clerc, Catherine; Gelu-Simeon, Moana; Piquet-Pellorce, Claire; Samson, Michel
Highlights: Hepatic impact of chronic co-exposure to chlordecone and CCl4 investigated in mouse model. Chlordecone enhances the liver damage in CCl4 murine chronic hepatitis. Chlordecone enhances the progression of liver fibrosis in mice. Abstract: Chronic liver damage due to viral or chemical agents leads to a repair process resulting in hepatic fibrosis. Fibrosis may lead to cirrhosis, which may progress to liver cancer or a loss of liver function, with an associated risk of liver failure and death. Chlordecone is a chlorinated pesticide used in the 1990s. It is not itself hepatotoxic, but its metabolism in the liver triggers hepatomegaly and potentiates hepatotoxic agents. Chlordecone is now banned, but it persists in soil and water, resulting in an ongoing public health problem in the Caribbean area. We assessed the probable impact of chlordecone on the progression of liver fibrosis in the population of contaminated areas, by developing a mouse model of chronic co-exposure to chlordecone and a hepatotoxic agent, carbon tetrachloride (CCl4 ). After repeated administrations of chlordecone and CCl4 by gavage over a 12-week period, we checked for liver damage in the exposed mice, by determining serum liver transaminase (AST, ALT) levels, histological examinations of the liver and measuring the expression of genes encoding extracellular matrix components. The co-exposure of mice to CCl4 and chlordecone resulted in significant increases in ALT and AST levels. Chlordecone also increased expression of the Col1A2, MMP-2, TIMP-1 and PAI-1 genes in CCl4 -treated mice. Finally, we demonstrated, by quantifying areas of collagen deposition and alpha-SMA gene expression, that chlordecone potentiated the hepatic fibrosis induced by CCl4 . In conclusion, our data suggest that chlordecone potentiates hepatic fibrosis in mice with CCl4 -induced chronic liver injury.